Minimal Clinically Important Difference for Three Quality of Recovery Scales. (July 2016) - Myles, Paul S.; Myles, Daniel B.; Galagher, Wendy; Chew, Colleen; MacDonald, Neil; Dennis, Alicia
Abstract : Background: Several quality of recovery (QoR) health status scales have been developed to quantify the patient's experience after anesthesia and surgery, but to date, it is unclear what constitutes the minimal clinically important difference (MCID). That is, what minimal change in score would indicate a meaningful change in a patient's health status? Methods: The authors enrolled a sequential, unselected cohort of patients recovering from surgery and used three QoR scales (the 9-item QoR score, the 15-item QoR-15, and the 40-item QoR-40) to quantify a patient's recovery after surgery and anesthesia. The authors compared changes in patient QoR scores with a global rating of change questionnaire using an anchor-based method and three distribution-based methods (0.3 SD, standard error of the measurement, and 5% range). The authors then averaged the change estimates to determine the MCID for each QoR scale. Results: The authors enrolled 204 patients at the first postoperative visit, and 199 were available for a second interview; a further 24 patients were available at the third interview. The QoR scores improved significantly between the first two interviews. Triangulation of distribution- and anchor-based methods results in an MCID of 0.92, 8.0, and 6.3 for the QoR score, QoR-15, and QoR-40, respectively. Conclusion: Perioperative interventions that result in a change of 0.9 for the QoR score, 8.0 for the QoR-15, or 6.3 for the QoR-40 signify a clinically important improvement or deterioration. Abstract : In a study of 204 patients, the minimum clinically meaningful differences in the quality of recovery scales were 0.9, 8.0, and 6.3 for the 9-, 15-, and 40-item versions, respectively.Supplemental Digital Content is available in the text.